In Silico Analysis and Transcriptional Profiling of A Putative Metalloprotease ADAMTSL as A Potential Tick Antigen against Rhipicephalus microplus - Cesar Onoshi Sedano-Juarez; Ninnet Gómez-Romero; Miguel Ángel Alonso-Díaz; América Ivette Barrera-Molina; David Emanuel Reyes-Guerrero; Rodolfo Lagunes-Quintanilla (Pathogens)
The cattle tick, Rhipicephalus microplus, is the most significant ectoparasite in the cattle industry. The application of acaricides constitutes the main control method. However, inadequate treatments have serious drawbacks, including the appearance of multi-resistant ticks. Tick vaccines offer a safe and economically sustainable alternative for controlling R. microplus. Nevertheless, the efficacy of existing vaccines has been limited by polymorphisms in target antigens among strains from different geographical regions. In this study, we characterized a putative Metalloprotease from the ADAMTSL family. We analyzed three regions to evaluate their transcriptional profiling in different R. microplus tick tissues, using two constitutive genes (β-tubulin and Elfa-1) as references. The expression levels showed that ADAMTSL-R1 was upregulated 39.37-fold (p ≤ 0.05) in salivary glands. The ADAMTSL-R2 showed the highest expression, rising 7.69-fold (p ≤ 0.05) in ovaries and up to 59.39-fold (p ≤ 0.05) in egg mass. Furthermore, this region showed the highest level of conservation among Rhipicephalus isolates. The ADAMTSL-R3 was upregulated only in the egg mass. The results of this study provide a basis for future research focused on elucidating the role of these protein variants in tick biology, including their feeding mechanisms and potential implications in pathogen transmission. Understanding these factors may aid in developing an effective tick vaccine.